HISTORY OF THE EMERGENCE AND DEVELOPMENT OF THE CONCEPTS OF “COMPETENCE” AND “COMPETENCY” (Web of Teachers: Inderscience Research, 2023)
In this article, it was studied from where and how the concepts of "competence" and "competence" appeared. The criteria for assessing the competence of a teacher are presented, pedagogical experiments are described.